DISKRESI PENYIDIK KEPOLISIAN DALAM PENYELESAIAN PERKARA PIDANA MELAUI JALUR NON LITIGASI - Udin Latif (Prodi Akhwal Syahsiyyah IAIN Sorong, 2023)
Law enforcers in the Criminal Justice System are tasked with enforcing the law and aiming to tackle, prevent or foster and reduce the occurrence of crimes or violations of criminal law, as well as making people's lives safe, peaceful, controlled and synergistic. Each component in the Criminal Justice system has the authority to screen cases starting at the investigative level in the form of police action which in practice is called investigator discretion. Police investigators use their discretionary authority to make efforts to settle cases outside the criminal justice system. The process of terminating an investigation carried out by an investigator is a form of police discretion, namely an authority exercised by the police based on their judgments and beliefs by prioritizing moral considerations rather than legal considerations.